Recent Insights into Breast Cancer Metastasis: Molecular Pathways, Prognostic Markers and Novel Therapies - Bhadange Jyoti A,; Dr. Shekhar V. Kokate, (Asian Journal of Pharmaceutical Research and Development, 2026)
Breast cancer metastasis remains a major challenge, contributing significantly to its high mortality rate despite progress in early diagnosis and localized treatments. This review consolidates recent advancements in three crucial areas: molecular mechanisms underlying metastatic progression, prognostic biomarkers for disease prediction, and emerging therapeutic strategiestargetingmetastasis. Keysignaling pathways, including MAPK,PI3K/AKT/mTOR, and Wnt/β-catenin, as well as tumor microenvironment interactions and epithelial-mesenchymal transition, are explored for their role in tumor dissemination and colonization of distant organs. The discovery of prognostic markers such as circulating tumor cells (CTCs), exosomal micro RNAs, cell-free DNA, and genetic alterations like BRCA1/2 mutations and HER2 amplification has revolutionized precision oncology by enabling real-time disease monitoring and patient stratification. Additionally, advancements in transcriptomic and proteomic profiling have introduced novel biomarkers that enhance metastaticrisk assessment and therapeutic decision-making. In parallel, innovative treatment approaches offer new prospects for managing metastatic breast cancer. Immunotherapy strategies, including cancer vaccines, immune checkpoint inhibitors, and adoptive cell therapies, are reshaping treatment paradigms, while targeted small-molecule inhibitors, such as PARP and CDK4/6 inhibitors, alongwith nanotechnology-based drug delivery systems, are improving therapeutic efficacy while minimizing adverse effects. However, challenges such as tumor heterogeneity, resistance to therapy, and variable patient responses highlight the need for further research and clinical trials. By bridging molecular insights with clinical applications, this review aims to provide a comprehen sivere source on the evolving land scape of metastatic breast cancer, focusing on molecular mechanisms, prognostic advancements, and novel therapeutic developments.